DISKRESI HAKIM DALAM MENETAPKAN HUKUM DI PENGADILAN AGAMA KELAS IB BATUSANGKAR - Yunarti, Sri (JURIS (Jurnal Ilmiah Syariah), 2017)
So far the verdict courts made by Pengadilan Agama (PA/ Family Court) have been criticized for being too fixated on legal justice approaches and lack of attention to social justice approaches. This criticism demands that judge's understanding of the law holds to the spirit that underlies the formation of the law. The judge needs to use his or her authority to exercise legal discretion, using more moral rather than formal legal ideas. A judge must understand the law in the right contest and act as a creative lawyer. Discretion is the authority of the judge to decide cases with more consideration of the senseof justice, public interest and morality, which develops in society rather than deciding on the basis of the decisions of the regulations contained in the Law. This authority can be used an alternative in response to the absence and weaknesses in the application of legal principles in Civil Law System. Thus the law is expected to play a maximum role to serve the interests of the dynamic community put the interests of both parties who are in dispute and growing as well.